1994
DOI: 10.1182/blood.v84.4.1074.bloodjournal8441074
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor GATA-2 is expressed in erythroid, early myeloid, and CD34+ human leukemia-derived cell lines

Abstract: To understand the functional roles that the GATA factors may play during hematopoietic cell differentiation, we examined the expression of GATA factor mRNAs and protein products in various human cell lines. Blot hybridization analyses demonstrated that GATA-1 and GATA-2 mRNAs are expressed abundantly in a set of cell lines established from human myelogenous leukemia cells, but the expression pattern of each factor is distinct. GATA-2 mRNA is expressed in all cell lines tested that express erythroid markers, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 0 publications
1
28
0
1
Order By: Relevance
“…The expression profile of GATA-2 originally suggested that this factor contributes to the transcriptional activation of a group of genes specifically expressed in early stage haematopoietic progenitor cells (Leonard et al 1993a;Nagai et al 1994). GATA-2 mRNA was also found in cells differentiating along the erythroid, megakaryocytic and mast cell lineage pathways (Yamamoto et al 1990;Zon et al 1991;Dorfman et al 1992).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression profile of GATA-2 originally suggested that this factor contributes to the transcriptional activation of a group of genes specifically expressed in early stage haematopoietic progenitor cells (Leonard et al 1993a;Nagai et al 1994). GATA-2 mRNA was also found in cells differentiating along the erythroid, megakaryocytic and mast cell lineage pathways (Yamamoto et al 1990;Zon et al 1991;Dorfman et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…To perform RNA blot hybridization analysis, we first isolated cDNA clones encoding mouse GATA-2. We screened a foetal mouse liver cDNA library using a partial human GATA-2 cDNA clone (Nagai et al 1994). One clone (pmG2a) bearing the entire coding region of mGATA-2 was isolated (data not shown; DDBJ/GENBANK/EMBL accession number: AB000096), and this clone was used for RNA blot analysis.…”
Section: Gata-2 Mrna Is Abundant In Mouse Mast Cell Lines As Well As mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the precise roles of GATA1 on mast cell development have not been fully elucidated, previous studies showed that the reduced expression of GATA1 by targeted disruption of an upstream enhancer results in the formation of abnormal progenitors that differentiate into erythroid cells, megakaryocytes and mast cells (Migliaccio et al 2003;Ghinassi et al 2007). GATA2 is expressed in hematopoietic stem cells and multilineage progenitors and plays key roles in the maintenance and proliferation of those cells (Nagai et al 1994;Minegishi et al 1998Minegishi et al , 1999. Although the early embryonic lethality observed in Gata2 null mice (Tsai et al 1994) has precluded studies of Gata2 deficiency in mast cells in vivo, in vitro differentiation studies of embryonic stem (ES) cells have demonstrated that GATA2-deficient ES cells lose the ability to differentiate into mast cells (Tsai & Orkin 1997).…”
Section: Introductionmentioning
confidence: 99%
“…GATA-2 is abundantly expressed in immature erythroid progenitors and declines over the course of maturation. It is also found in other cell types [32,33]. Studies on GATA-2 deficient mice have shown that it plays an important role during the early stages of erythropoiesis.…”
Section: Gata-2mentioning
confidence: 99%